Odpowiedzi

Najlepsza Odpowiedź!
2009-11-16T20:27:07+01:00
(x+5)(x-2) = x²-2x+5x-10 = x² +3x - 10

x+3/2 * (w-3) = xw - 3x +3w - 9 /2

(x+x+2)*(x+1)/2 = 2x² + 2x +2x + 2 /2 = x² + 2x + 1
113 4 113
2009-11-16T20:35:01+01:00
A) prostokąta o bokach x+5 i x-2
P=(x+5)*(x-2)=xdo2-2x+5x-10=xdo2+3x-10

b) trójkąta o podstawie x+3 i wysokości w-3
P=(x+3)*(w-3)/2=(xw-3x+3w-9)/2
c) trapezu o podstawach x, x+2 i wysokości x+1
P=(x+x+2)*(x+1)/2=(2x+2)(x+1)/=(2xdo2+2x+2x+2)/2=(2xdo2+4x+2)/2=2(xdo2+2x+1)/2=xdo2+2x+1
38 3 38